Description of the male Hymenoepimecis japi Sobczak et al. 2009 (Hymenoptera, Ichneumonidae) parasitoid of Leucauge roseosignata Mello-Leitão 1943 (Araneae: Tetragnathidae) - JF. Sobczak (Brazilian Journal of Biology)
The male of Hymenoepimecis japi (Hymenoptera, Ichneumonidae, Pimplinae) is described and illustrated. The specimen was collected in a modified web (cocoon web) of Leucauge roseosignata (Araneae, Tetragnathidae) made in a laboratory. Both, host and parasitoid were collected in Reserva Biológica Serra do Japi, located in Jundiaí, São Paulo, Brazil.